Unearthing digital financial services and financial inclusion: an empirical evidence from India. (5th December 2019) - Nagpal, Aishwarya; Jain, Megha; Jain, Abhay
The present study aims at determining the role of information and communication technologies (ICTs), macroeconomic and demographic characteristics of individuals in advancing financial inclusion levels in India. Financial inclusion has been proxied by credit penetration, account ownership and digital financial services by key digital modes (i.e., mobile cellular subscriptions and internet penetration). The secondary data have empirically been analysed by using ordinary least squares estimation at the macro-level and employing logistic regression at the micro-level. The findings suggest that internet usage and mobile penetration rates have a positive association with financial inclusion in India. The study further discovers that individual characteristics and economic circumstances like education level, income level, age, gender, government transfers and saving behaviour are also likely to impact financial inclusion indicators in India. Unearthing a perfect balance between adopting an inclusive financial approach, pro-poor growth, and a technologically advanced infrastructure is indispensable for each facet that has an important role to contribute. Finally, the study recommends that such moves are not an end in themselves, rather expected to shoulder the responsibility of creating new economic order in India via financial inclusion toolbox through sustainable development goals (SDGs).